THE ROLE OF EXPLICIT INSTRUCTION IN ENGLISH WORD STRESS PATTERNS IN AN EFL ARAB UNIVERSITY CONTEXT - M. Mosheer Amer; Walid M. Amer (Indonesian JELT, 2011)
This study presents the results of an investigation into the extent to which explicit instruction in English word stress patterns correlates with better word stress assignment performance by Palestinian EFL university students. The students received three weeks of explicit instruction in the main English word stress rules. In analyzing the differences in the pre- and post-treatment test scores, the researchers found significant increases on the post-treatment test scores which indicate a correlation between explicit instruction in word stress rules and students' performance in word stress assignment. Teaching suggestions and activities are provided to improve learners' word stress assignment performance. The results of this study are of great value to Palestinian linguists, EFL teachers and curricula developers who need to pay special attention to this often overlooked area and, therefore, to ensure that pedagogical materials and teaching activities on word stress become an integral part of EFL curricula. Keywords:   word stress – explicit instruction – Arab EFL learners – stress placement rules